2007
DOI: 10.2527/jas.2006-292
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and in situ dry matter and fiber disappearance of sorghum × Sudangrass hybrids1

Abstract: Three sorghum x Sudangrass hybrids were planted in twelve 0.2-ha plots to test the effect of date of harvest and hybrid on plant maturity, DM yield, chemical composition, and in situ DM and fiber disappearance. Sweet Sunny Sue (a non-brown midrib (BMR) hybrid; nonBMR), NutriPlus BMR (a BMR hybrid; NP-BMR), and Dry Stalk BMR (a BMR hybrid; DS-BMR) were planted on 26 June 2003 at 22.4 kg of seed/ha. Beginning 34 d after planting, plant height and phenological growth stage were assessed weekly in 10 random, 0.5-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 11 publications
4
36
0
6
Order By: Relevance
“…Beck et al (2007) observed CP content of 12.6; 9.7; 6.9; 5.0 and 4.3% when a sorghum-Sudan grass hybrid was subjected to cutting at 34, 41, 48, 55 and 63 days after planting, respectively. Nineteen hybrids analyzed had ideal values of CP content to meet the requirements of nitrogen by rumen flora and for a good rumen functioning (7% minimum).…”
Section: Methodsmentioning
confidence: 90%
“…Beck et al (2007) observed CP content of 12.6; 9.7; 6.9; 5.0 and 4.3% when a sorghum-Sudan grass hybrid was subjected to cutting at 34, 41, 48, 55 and 63 days after planting, respectively. Nineteen hybrids analyzed had ideal values of CP content to meet the requirements of nitrogen by rumen flora and for a good rumen functioning (7% minimum).…”
Section: Methodsmentioning
confidence: 90%
“…Beck et al (2007) A mutação bmr-6 provocou reduções de 9,5; 12,4 e 11,1% nos teores de FDA da planta inteira nas idades de 52, 61 e 67 dias, respectivamente, ao passo que na idade de 74 dias não foram observadas diferenças entre os híbridos que compõem o par isogênico normal e mutante bmr. Beck et al (2007) (1988), ao avaliarem as silagens e os fenos produzidos com dois híbridos de sorgo com capim-sudão convencionais e seus pares isogênicos portadores de nervura marrom, não observaram redução nos teores de FDA em função da mutação bmr.…”
Section: Idade Ao Corte (Dias)unclassified
“…Beck et al (2007) A mutação bmr-6 provocou reduções de 9,5; 12,4 e 11,1% nos teores de FDA da planta inteira nas idades de 52, 61 e 67 dias, respectivamente, ao passo que na idade de 74 dias não foram observadas diferenças entre os híbridos que compõem o par isogênico normal e mutante bmr. Beck et al (2007) (1988), ao avaliarem as silagens e os fenos produzidos com dois híbridos de sorgo com capim-sudão convencionais e seus pares isogênicos portadores de nervura marrom, não observaram redução nos teores de FDA em função da mutação bmr. As variações observadas nos efeitos das mutações bmr entre experimentos corroboram com a colocação de Cherney et al (1991) de que a expressão das mutações bmr são frequentemente modificadas pelo ambiente e pela linhagem de células em que ela é expressada, e justifica a importância de se testar os efeitos desses genes em ambientes e linhagens diversos.…”
Section: Idade Ao Corte (Dias)unclassified
See 2 more Smart Citations